Students' Misconceptions and the Causes on Straight Motion Materials Using Six-Tier Multiple Choice - Dewi Ratna Sari; Fatni Mufit (Postgraduate, University of Mataram, 2023)
In physics learning, often encountered misconceptions experienced by students, one of which is in the material of straight motion. In addition to misconceptions, the causes of misconceptions also need to be known by the teacher. By knowing the misconceptions and their causes that occur to students so that teachers can improve the learning process and improve student learning outcomes. This study aims to analyze the profile of students' misconceptions and their causes in the material of straight motion. The instrument used in identifying misconceptions and their causes is Six-Tier Multiple Choice which consists of 17 multiple choice questions at six levels. The type of research used is descriptive research with a quantitative approach. ThÂe population in this study were students of class X MIPA SMA Negeri in Regency of Solok Selatan. The sample in this study were three schools with high, medium and low categories in Regency of Solok Selatan with a total sample of 195 students. Sampling in this study used a purposive sampling technique. Overall, the results of the study at SMA Solok Selatan Regency found that misconceptions were classified as low at 19.37%. The results showed that 17.57% of misconceptions occurred in SMA A, 21.48% in SMA B and 18.09% in SMA C. The highest misconceptions occurred in schools with moderate categories, followed by schools with low categories and schools with high categories. The main cause of misconceptions is the personal thinking of students with a percentage of 42.50%.